Case Report: The Association Between Chromosomal Anomalies and Cluster A Personality Disorders: The Case of Two Siblings With 16p11.2 Deletion and a Review of the Literature - Esposito, Cecilia Maria; Enrico, Paolo; Sciortino, Domenico; Caletti, Elisabetta; Marchetti, Giulia Bruna; Cesaretti, Claudia; Oldani, Lucio; Fiorentini, Alessio; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
Although several studies have shown the correlation between chromosomal rearrangements and the risk of developing psychotic disorders, such as Schizophrenia, little attention has been given to identifying the genetic basis of predisposing personality so far. In this regard, a limited but significant number of studies seems to indicate an association between chromosomal anomalies and cluster A personality disorders (CAPD). Starting from the clinical description of two brothers affected by familial 16p11 deletion syndrome (OMIM #611913), both sharing cluster A and C personality traits, the aim of the present study is to critically review the literature regarding the correlation between chromosomal rearrangements and CAPD. A bibliographic search on PubMed has been conducted and 8 studies were finally included in our review. Most of the studies highlights the presence of schizotypal personality disorder in 22q11.2 deletion syndrome, whose evolutionary course towards psychotic pictures is well known. One study also identified a paranoid personality disorder in a patient with a deletion on chromosome 7q21.3. No studies have so far identified the presence of paranoid personality disorder in 16p11 deletion, as in the case of the two siblings we report, while its association with psychosis and autism is already known. Although further epidemiologic studies on broader populations are indicated, our observations might pave the way for the definition of new diagnostic subgroups of CAPD and psychotic disorders, in order to implement the clinical management of such complex conditions.